2015
DOI: 10.1002/tox.22176
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine exposure to bisphenol A promotes different effects in both neonatal and adult prostate of male and female gerbils (Meriones unguiculatus)

Abstract: Substances that mimic endogenous hormones may alter the cell signaling that govern prostate development and predispose it to developing lesions in adult and senile life. Bisphenol A is able to mimic estrogens, and studies have demonstrated that low levels of exposure to this compound have caused alterations during prostate development. The aim of this study was to describe the prostate development in both male and female neonatal gerbils in normal conditions and under exposure to BPA during intrauterine life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…As in males, the female prostatic epithelial buds arise from the UGS, invade the pm around the urethral epithelium, and elongate inside this mesenchymal tissue towards the paraurethral mesenchyme (pam), a condensed mesenchymal tissue in which the buds start to undergo branching morphogenesis. Although the understanding of the initial female prostate organogenesis is still incomplete, some recent studies of our research group have highlighted important aspects of the female prostate development (de Lima et al, ; Rodríguez et al, ) (Figures a and 2b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in males, the female prostatic epithelial buds arise from the UGS, invade the pm around the urethral epithelium, and elongate inside this mesenchymal tissue towards the paraurethral mesenchyme (pam), a condensed mesenchymal tissue in which the buds start to undergo branching morphogenesis. Although the understanding of the initial female prostate organogenesis is still incomplete, some recent studies of our research group have highlighted important aspects of the female prostate development (de Lima et al, ; Rodríguez et al, ) (Figures a and 2b).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these aspects should be considered nowadays, mainly because we are more exposed to exogenous substances, such as endocrine‐disrupting chemicals (EDCs), that may disrupt and predispose the gland to the development of diseases with aging (Biancardi et al, ; Perez et al, ). A wealth of experimental analyses from our research group employing gerbils has shown that the female prostate is very sensitive to exogenous hormonal interference (Santos et al, ; Biancardi et al, , ; de Lima et al, ; Rodríguez et al, ; Perez et al, ). These studies have shown that the early exposure to exogenous substances, as specific hormones, for instance, increases the susceptibility to the development of prostatic lesions during aging in both male and female gerbils (Biancardi et al, , ; Perez et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fentanyl-propofol is a common intravenous anesthesia (19). However, respiratory depression of fentanyl during surgery is rather common and hyperpathia after surgery occurs frequently (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, respiratory depression of fentanyl during surgery is rather common and hyperpathia after surgery occurs frequently (19). Propofol is an alkylphenolsedative-hypnotic drug and its advantages include quick effects, short hold time and fast waking (20).…”
Section: Discussionmentioning
confidence: 99%